Clinical Effectiveness of (18)F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Management of Renal Cell Carcinoma: A Single Institution Experience - Win, Aung Zaw (World J Nucl Med, 2015)
Positron emission tomography (PET) is currently the most advanced technique of metabolic imaging available for tumor diagnosis and follow-up. The aim of this study was to examine the versatility and accuracy of fluorodeoxyglucose (FDG) PET/computed tomography (CT) in the metastasis detection of renal cell carcinoma (RCC). We also compared our findings to other similar studies from the literature. This is the biggest study so far to examine the sensitivity and specificity of FDG PET/CT in the management of RCC. A retrospective review was carried out on all the FDG PET/CT studies done from January 1999 to January 2014 at our institution. Biopsy results were considered the gold standard. For our patients (n = 315) with biopsy results, FDG PET/CT studies exhibited 100% sensitivity, 100% specificity. Our results were better than results achieved by other studies. The use of FDG PET/CT in restaging and metastasis detection of RCC has many advantages, in addition to high accuracy. This imaging technique has great potential in influencing treatment decisions. We recommend the incorporation of FDG PET/CT in routine standard protocols for RCC.